CTNNB1 Knockdown Inhibits Cell Proliferation and Aldosterone Secretion Through Inhibiting Wnt/β-Catenin Signaling in H295R Cells. (7th December 2020) - Zhou, Tingting; Luo, Pengwei; Wang, Liang; Yang, Shiwei; Qin, Shiyuan; Wei, Zhitao; Liu, Jiwen
Aldosterone-producing adenomas (APA) is one of the causative factors of primary aldosteronism. Previous studies have suggested that there are somatic CTNNB1 mutations in APA, but the specific mechanism of CTNNB1 mutation in APA tumorigenesis and aldosterone secretion remains unclear. In the present study, human adrenocortical carcinoma cell line H295 R was used to establish stable CTNNB1 knockdown cell lines. Cell proliferation and aldosterone secretion of H295 R cells in response to angiotensin Ⅱ (Agn Ⅱ) were analyzed. We found that CTNNB1 knockdown reduced β-catenin expression and inhibited proliferation of H295 R cells. CTNNB1 knockdown inhibited Wnt/β-catenin signaling pathway and downregulated expression of downstream genes including axin 2, lymphoid enhancer binding factor 1 ( LEF1 ), and cyclin D1. In addition, CTNNB1 knockdown decreased responses of H295 R cells to Agn Ⅱ and decreased aldosterone secretion. Our findings suggest that CTNNB1 knockdown can inhibit H295 R cell proliferation and decrease aldosterone secretion in the responses of H295 R cells to Ang II through inhibiting Wnt/β-catenin signaling pathway, indicating that targeting Wnt/β-catenin signaling pathway may be an important approach to decrease aldosterone secretion in the treatment of aldoster-producing adenomas.